Overview severity of malocclusion in children with special needs in SLB Negeri 1 Makassar: Gambaran tingkat keparahan maloklusi pada anak berkebutuhan khusus di SLB Negeri 1 Makassar - Ardiansyah S Pawinru; Nur Rahmadani Alimuddin; Susilowati (Makassar Dental Journal PDGI Makassar, 2024)
To determine the severity of malocclusion in children with special needs based on the period of mixed teeth and the period of permanent teeth in SLB Negeri 1 Makassar, a study was conducted using a cross-sectional study method with a descriptive observation design. Samples of children with special needs were taken by purposive sampling at SLB Negeri 1 Makassar with clinical examination using the Occlusion Feature Index. The results showed the severity of malocclusion in the period of mixed teeth as much as 59.5%, in the period of permanent teeth as much as 40.8%. In children with special needs, it was found that the category in dire need of orthodontic treatment was in the category of autistic disorders (85.7%) followed by the classifica-tion of disorders of tunagrahita (66.7%). While in the classification of blind disorders 46.7% did not need orthodontic treatment. It is concluded that malocclusion is more prevalent in children with special needs with the autistic disorder category.